Dissecting the rust resistance in salt tolerant wheat germplasm - Lata, Charu; Prasad, Pramod; Gangwar, Om P.; Kallugudi, Jayanth; Adhikari, Sneha; Manjul, Anshul Sharma; Kumar, Subodh; Kumar, Arvind; Kulshreshtha, Neeraj; Khippal, Anil; Tiwari, Ratan (Frontiers in Microbiology, 2024)
Wheat is one of the most important food crop cultivated across the globe which ensures sustainability and food security to massive world's population, but its production is threatened by both biotic factors like rust (caused by Puccinia species) and abiotic stresses such as salinity. In this study, 41 salt-tolerant wheat lines were screened for rust resistance at both seedling and adult plant stages. Rust resistance genes were characterized through gene matching and molecular markers. Yr2 was confirmed in twenty three lines, while Yr9 along with Lr26/Sr31 were postulated in six lines with the help of SRT and molecular markers.Except for KRL2013, none showed complete resistance to all Puccinia striiformis f. sp. tritici (Pst).Lr24/Sr24 genes were confirmed in HD2851 and KRL2029, and Lr13 was detected in a maximum of twenty four wheat lines, with varying reaction responses to different leaf rust pathotypes. Several lines carried additional resistance genes such as Sr11, Sr28, and Lr68. Lr68 an effective race non-specific APR gene identified in fifteen wheat lines with the help of CsGs-STS marker. Although many salt-tolerant wheat lines were susceptible to yellow rust during the seedling stage, a few lines showed APR in the years during 2020 and 2021. Three lines (KRL213, KRL219 and KRL238) showed complete resistance in adult plant stage to leaf rust. These findings offer insights into the genetic basis of rust resistance in salttolerant wheat, aiding breeding strategies.